Implementasi Bantuan Sosial Kartu Penyandang Disabilitas Jakarta dalam Upaya Memenuhi Kebutuhan Dasar Penyandang Disabilitas - Daniel Stefanus; Qotrun Nida; Aryanti Dwi Untari (JURNAL PENDIDIKAN DAN ILMU SOSIAL (JUPENDIS), 2026)
The problem of poverty in the Johar Baru area remains a serious challenge for the Government. Based on Law Number 13 of 2011 concerning Handling the Poor and Law Number 8 of 2016 concerning Persons with Disabilities, the state is obliged to provide protection and guarantee the rights of persons with disabilities. As an implementation at the regional level, the DKI Jakarta Provincial Government, through Governor Regulation Number 44 of 2022, implemented the Jakarta Disability Card (KPDJ) program, which is a non-cash social assistance of IDR 300,000.00 per month for residents with disabilities. This study aims to describe the implementation of the KPDJ program and analyze the extent to which the Government is able to meet the basic needs of persons with disabilities in the Johar Baru area. The study was conducted using a qualitative descriptive approach, with researchers as the main instrument. The results found that the implementation of the KPDJ program has not been running optimally, reflected in the amount of assistance that is still far below the standard of decent living needs, as well as the quota of beneficiaries and access to affordable food that is not evenly distributed. This research is expected to lead to a review of the amount of assistance, an expansion of recipient quotas, and strengthening cross-sector coordination so that people with disabilities can access all program benefits fairly and equitably.